Rínogenné flegmóny orbity - Droppa, J; Cechová, M; Cech, B (Ceskoslovenska otolaryngologie, 1990)
During the past 15 years we treated at the ENT department and ophthalmological department of the hospital with policlinic type III in Nitra 10 patients with orbital phlegmons or an abscess of the eyelid after an eye injury treated and cured by antibiotic treatment and external drainage. Twelve patients had a rhinogenic phlegmon or abscess in the orbit (one patient had a dentogenic aetiology of the inflammation). This group of 12 patients were treated in addition to antibiotics in different combinations also surgically (in one case also by drainage of the abscess from a lateral quadrant of the orbit). In five instances the authors found in addition to the phlegmon of the periorbital tissue also an abscess in the depth of the orbit and six times an abscess of the eyelid. Despite the radical approach to the inflammation of the paranasal sinuses and inflammation of the orbit, two patients developed blindness of the damaged eye and one patient died from rhinogenic suppurative meningitis.
Keywords: Infant; dospělí; Child, Preschool; Adult; lidé; nemoci orbity; bakteriální infekce; dítě; celulitis; předškolní dítě; Bacterial Infections; Child; Humans; Paranasal Sinus Diseases; kojenec; nemoci vedlejších nosních dutin; Cellulitis; Orbital Diseases